Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1186/1756-0500-7-379
|View full text |Cite
|
Sign up to set email alerts
|

BrassicaTED - a public database for utilization of miniature transposable elements in Brassica species

Abstract: BackgroundMITE, TRIM and SINEs are miniature form transposable elements (mTEs) that are ubiquitous and dispersed throughout entire plant genomes. Tens of thousands of members cause insertion polymorphism at both the inter- and intra- species level. Therefore, mTEs are valuable targets and resources for development of markers that can be utilized for breeding, genetic diversity and genome evolution studies. Taking advantage of the completely sequenced genomes of Brassica rapa and B. oleracea, characterization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Transposable elements were annotated in the B. rapa R‐o‐18 genome with RepeatMasker (v. 4‐0.5) using RMBlast and a combined library of exemplar repetitive DNA elements from the following sources: Brassica and Arabidopsis repetitive DNA elements from RepBase (http://www.girinst.org/repbase/) updated through vol17, issue 4; Brassica rapa RepeatModeler‐generated dataset (Cheng et al ., ); Arabidopsis thaliana transposons from TAIR10 (http://ftp://ftp.arabidopsis.org/home/tair/Genes/TAIR10_genome_release/, downloaded 3/27/2017); Brassica MITE, TRIM and SINEs (Murukarthick et al ., ); Brassica rapa MITEs (Chen et al ., ); and Brassica hATs (Nouroz et al ., ). As the RepeatModeler‐generated dataset of repetitive elements included 1037 unclassified elements, 176 of the unclassified elements were manually annotated and used to classify an additional 226 elements based on blastn hits with e‐values <1E‐10.…”
Section: Methodsmentioning
confidence: 99%
“…Transposable elements were annotated in the B. rapa R‐o‐18 genome with RepeatMasker (v. 4‐0.5) using RMBlast and a combined library of exemplar repetitive DNA elements from the following sources: Brassica and Arabidopsis repetitive DNA elements from RepBase (http://www.girinst.org/repbase/) updated through vol17, issue 4; Brassica rapa RepeatModeler‐generated dataset (Cheng et al ., ); Arabidopsis thaliana transposons from TAIR10 (http://ftp://ftp.arabidopsis.org/home/tair/Genes/TAIR10_genome_release/, downloaded 3/27/2017); Brassica MITE, TRIM and SINEs (Murukarthick et al ., ); Brassica rapa MITEs (Chen et al ., ); and Brassica hATs (Nouroz et al ., ). As the RepeatModeler‐generated dataset of repetitive elements included 1037 unclassified elements, 176 of the unclassified elements were manually annotated and used to classify an additional 226 elements based on blastn hits with e‐values <1E‐10.…”
Section: Methodsmentioning
confidence: 99%
“…oleracea (Bo-1-1) genome sequence was independently analyzed to identify the major REs using the abovementioned approach. Sequences of the individual repeat families for each species were stored in the Brassica TED 48 . In addition, graph-based clustering and characterization of repetitive elements by RepeatExplorer was performed using the 0.1x WGS reads from each B .…”
Section: Methodsmentioning
confidence: 99%
“…TRIM families are distributed throughout the B. rapa and B. oleracea genomes . Though the insertions of five Brassica TRIM families were random, Genome-wide characterization showed that 619 (44 %) and 656 (40 %) of the members of the five Brassica TRIM families reside in or within 2 kb of a gene in the B. rapa and B. oleracea genome, respectively (Yang et al 2007;Murukarthick et al 2014;Table 6.2). Most-TRIM families are present in relatively similar copy numbers between Brassica species but the Cassandra family appears to show high divergence between B. rapa and B. oleracea, based on members found in counterpart paralogous sequences of pseudo-chromosomes (Sampath and Yang 2014a, b).…”
Section: Characteristics and Distribution Of Mtesmentioning
confidence: 99%